Farmers’ Finger Millet [Eleusine coracana (L.) Gaertn] Seed Management Practices in West Gojjam Zone, Northwestern Ethiopia - Getahun, Wossen Tarekegne; Mekbib, Firew; Dessalegn, Yigzaw (Journal of Agriculture and Environmental Sciences, 2021)
Finger millet is one of the major growing crops in Amhara region particularly in West Gojjam Zone in maintaining food and nutrition security. However, the quality of finger millet seeds, agronomic packages and the productivity of the crop is very low as well as maintaining of genetic diversity is not documented. The present study was carried out in Yilmana-Densa and Mecha districts of Northwestern Ethiopia to document farmers’ knowledge and experiences on finger millet seed management practices. Data were collected from 120 households using a structured questionnaire and focus group discussion. The results showed that 72.5% of the respondents explained that seed selection is made by both husband and wife; and the seed was selected soon after threshing 58.3% of the respondents replied that the seeding materials are selected soon after threshing while 37.5% did during planting time. Almost all respondents used locale made materials to clean seed and 97.5% of them didn’t use storage chemicals as finger millet do have a long shelf life like teff. Nowadays farmers used improved varieties of finger millet as its productivity is better than the local varieties. Therefore, the existing finger millet seed management practices has been contributing for maintaining genetic diversity, however, the system is insufficient to hold and enhance the existing function of the extension organization, farmer cooperative union, NGO and government organization to meet the seed quality thereby seed security. Hence, establishing and strengthening linkages among stakeholders to use indigenous knowledge on seed management practices, seed selection, diversity conservation and seed security for a bad time.